Low-density extraction solvent-based solvent terminated dispersive liquid–liquid microextraction combined with gas chromatography-tandem mass spectrometry for the determination of carbamate pesticides in water samples - Chen, Hao; Chen, Ruiwen; Li, Shengqing (Journal of Chromatography A, 2010)
A simple and fast method of low-density extraction solvent-based solvent terminated dispersive liquid–liquid microextraction (ST-DLLME) was developed for the highly sensitive determination of carbamate pesticides in the water samples by gas chromatography-tandem mass spectrometry (GC-MSMS). After dispersing, the obtained emulsion cleared into two phases quickly when an aliquot of acetonitrile was introduced as a chemical demulsifier into the aqueous bulk. Therefore, the developed procedure does not need centrifugation to achieve phase separation. It was convenient for the usage of low-density extraction solvents in DLLME. Under the optimized conditions, the limits of detection for all target carbamate pesticides were in range of 0.001–0.50 ng mL −1 and the precisions were in the range of 2.3–6.8% (RSDs, 2 ng mL −1, n = 5). The proposed method has been successfully applied to the analysis of real water samples and good spiked recoveries over the range of 94.5–104% were obtained.